What drives fossil fuel consumption in Indonesia? Evidence from a macroeconomic perspective - Kamal Fachrurrozi; Aliasuddin Aliasuddin; Wisnu Satria; Mirzatul Kadri; Ichwan Ichwan (Nur Science Institute, 2026)
Fossil fuels play a crucial role in economic activity in developing countries, including Indonesia. Currently, fossil fuels dominate and serve as the primary energy source, accounting for approximately 80% of the country's energy needs. Amidst fluctuating macroeconomic dynamics, fossil fuel consumption has experienced a significant increase. In this paper, we investigate the effects of macroeconomic indicators, namely economic growth, urbanization, and trade openness, on fossil fuel consumption in Indonesia. The study uses data from 1990 to 2024 sourced from Our World in Data and the World Bank. The analysis used multiple linear regression to examine the influence between variables, along with classical assumption tests. The study found that economic growth had a positive and significant effect. Urbanization had a positive and significant effect. Trade openness was also found to have a positive and significant effect on fossil fuel consumption. The largest increase in fossil fuel consumption was driven by urbanization. These findings have important implications for the formulation of future energy policies.